Designing for Change in Networked Learning Environments
XX, 536 p.
Keywords: Designing for Learning in Networked Learning Environments is of interest to researchers and students, designers, educators, and industrial trainers across various disciplines including education, cognitive, social and educational psychology, didactics, computer science, linguistics and semiotics, speech communication, anthropology, sociology and design. Computer Support for Collaborative Learning (CSCL) is a genuinely interdisciplinary field that strives to create a better understanding of collaborative learning that is mediated by a diverse set of computational technologies. The theme of CSCL 2003 "Designing for Change in Networked Learning Environments" reflects a commitment to influence educational practice in times of the Internet. The contributions in this volume include discussions on knowledge building, designing and analysing group interaction, design of collaborative multimedia and 3D environments, computational modelling and analysis, software agents, and much more.